Analisis Strategi Pemasaran Produk Digital CRM di PT Infomedia Nusantara - Erlina Aduski; Prasetyo Hadi; Rusdi Musa Ishaq (MBIA, 2020)
The purpose of this research is to reformulate the marketing strategy of Digital CRM products where at this time, in the digital era, the contribution of revenue generated by CRM Digital is still very low if we compared with Inbound Call (Legacy CRM). This research applied the qualitative approach with a descriptive type of research and using PEST analysis, Industry Environment 5 Forces Porter Analysis, SWOT, and 7P Marketing Mix. Based on the analysis of external and internal factors, we get several alternative strategies such as 1) Product: focus on offering Integrated Omnichannel products, offering CRM as Managed Service; increasing maturity of application or platform and providing analytics enablers as a competitive advantage, 2) Price: implementing a flexible business scheme and conducting cost leadership, 3) Place: maximizing Telkom's Customer Facing Unit (CFUE) for marketing channels and doing global penetration, 4) People: building capabilities and competencies through training and certification 4) Process: make transformation process from conventional into automation, cognitive and Artificial Intelligence; Collaborate with partners to build a digital platform, robotics, and analytics 5) Promotion: creating brand awareness, channel awareness and focus on internal promotion at TelkomGroup. Abstrak Penelitian ini bertujuan untuk mengetahui existing strategi pemasaran produk Digital CRM dan merumuskan ulang strategi pemasaran berdasarkan alternatif strategi yang diusulkan. Pendekatan penelitian yang digunakan adalah kualitatif dengan jenis penelitian deskriptif yang menggunakan analisis faktor eksternal dan internal yaitu Analisis PEST, Analisis Lingkungan Industri 5 Forces Porter, 7S Mckinsey, SWOT, STP dan Bauran Pemasaran 7P. Alternatif Strategi yang diusulkan: 1) Product: fokus pada produk Integrated Omnichannel, menawarkan layanan CRM sebagai Managed Service, peningkatan maturity dari segi aplikasi /platform dan memberikan analytics enabler sebagai bentuk competitive advantage, 2) Price: Merapkan flexible business scheme dan melakukan Cost Leadership, 3) Place: memaksimalkan Customer Facing Unit Enterprise (CFUE) Telkom untuk channel pemasaran , melakukan penetrasi Global 4) People : membangun kemampuan dan kompetensi melalui training, sertifikasi, dan sharing session; redefine job roles, pembuatan kebijakan project delivery, mengembangkan roadmap untuk operational talent, 5) Promotion: meng-create Brand Awareness, and Channel Awareness serta fokus melakukan promosi di internal TelkomGroup. Kata kunci : Strategi Pemasaran; Analisis PEST, 5 Forces Porter, SWOT, Bauran Pemasaran 7P.